STRUCTURAL APPROACH AND PARTICIPATION OF LOCAL ACTORS IN MAINTAINING INTERFAITH HARMONY IN KUALA TUNGKAL, WEST TANJUNG JABUNG REGENCY - Rafii, Muhammad; Hatta, Juparno; Ilham, Muhammad; Br Surbakti, Junita; Amin, Muhammad (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
This article focuses on examining structur contributions in the community and the participation of local actors in maintaining religious harmony in Kuala Tungkal. This article uses qualitative research methods, data obtained through observation, interviews, and documentation. Data analysis was conducted by following the stages: data reduction, data presentation, and data verification. This article finds that the contribution of the structural approach in maintaining religious harmony is inseparable in managing religious harmony. Structures in society, religious organizations, religious institutions, pesantren, and the government have become systemic networks that can collaborate in social work, especially maintaining religious harmony. This can be maintained if there are local actors who have power and interest in religious harmony. Local actors become an important and strategic consideration as a figure and are considered a person who practices religious teachings and can be a role model for their worshipers. Therefore, this article concludes that the elite-structural approach is not relevant if it is only carried out separately, but must involve local non-structural actors who have complementary roles in mobilizing society and peacemaking.